The bisphosphonate incadronate (YM175) causes apoptosis of human myeloma cells in vitro by inhibiting the mevalonate pathway. - Shipman, C; Croucher, P; Russell, R; Helfrich, M; Rogers, M (1998)
It has recently been suggested that bisphosphonates may have direct antitumor effects in vivo, in addition to their therapeutic antiresorptive properties. Bisphosphonates can inhibit proliferation and cause apoptosis in human myeloma cells in vitro. In macrophages, bisphosphonate-induced apoptosis was recently found to be a result of inhibition of the mevalonate (MVA) pathway. The aim of this study was to determine whether bisphosphonates also affect human myeloma cells in vitro by inhibiting the MVA pathway. Incadronate and mevastatin (a known inhibitor of the MVA pathway) caused apoptosis in JJN-3 myeloma cells and inhibited cell proliferation. Geranylgeraniol and farnesol prevented incadronate-induced apoptosis and had a partial effect on cell cycle arrest. MVA and geranylgeraniol prevented mevastatin-induced apoptosis and inhibition of proliferation and completely prevented the effect of mevastatin on the cell cycle. These observations demonstrate that incadronate-induced apoptosis in human myeloma cells in vitro is the result of inhibition of the MVA pathway.